Hubungan Pengetahuan dan Sikap Masyarakat dengan Upaya Pencegahan Tuberkulosis Paru - Defa Miftahul Jannah Khairunnisa; Hasyim Kadri; Dwi Kartika Pebrianti; Marnila Yesni; Rahmi Dwi Yanti; Armina Armina; Dwi Yunita Rahmadhani (Jurnal Akademika Baiturrahim Jambi, 2023)
Tuberculosis is still a very widespread disease found in developing countries such as Indonesia in both children and adults, which is also a source of infection. This disease is easily transmitted through droplets of people infected with bacilli. The purpose of this study was to determine whether there was a relationship between knowledge and attitudes toward pulmonary tuberculosis prevention efforts in Legok Village, Jambi City. This research is a quantitative descriptive study with a correlational design. The sample was taken by accidental random sampling and using a questionnaire instrument. This research was conducted on 9-11 August 2022 in Legok Village, Jambi City. The population in this study was the entire community in Legok Village; the results of the study were analyzed univariately and bivariately using the Spearman Rank test. Based on the research, it was found that from 30 respondents, knowledge had a correlation coefficient of 0.73. From 30 respondents, attitudes had a correlation coefficient of 0.45. It was concluded that there was a relationship between knowledge and efforts to prevent pulmonary tuberculosis in Legok Village, Jambi City. There is a relationship between attitudes and efforts to prevent pulmonary tuberculosis in Legok Village, Jambi City